2017
DOI: 10.1038/nm.4391
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific disease-associated modules for depression

Abstract: A recent study reveals sexually dimorphic disease-associated gene-expression modules and hub genes in postmortem brains from female and male individuals with depression. These modules are conserved in mouse models of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Females had two-to three-fold higher rates of depression than males, as previously reported ( 61), of which several explanations have been offered: (1) Sexual dimorphism at the transcriptional level mediates gender-specific stress susceptibility (62). (2) Gender-related differences in neurotransmitter, endocrine, and metabolic systems result in differences in mood susceptibility (61). Our results from the stratified analyses revealed that, as we hypothesized, females had higher odds of probable LLD than males in the older population who were classified at the same IMCPR grade.…”
Section: Discussionsupporting
confidence: 58%
“…Females had two-to three-fold higher rates of depression than males, as previously reported ( 61), of which several explanations have been offered: (1) Sexual dimorphism at the transcriptional level mediates gender-specific stress susceptibility (62). (2) Gender-related differences in neurotransmitter, endocrine, and metabolic systems result in differences in mood susceptibility (61). Our results from the stratified analyses revealed that, as we hypothesized, females had higher odds of probable LLD than males in the older population who were classified at the same IMCPR grade.…”
Section: Discussionsupporting
confidence: 58%
“…Nevertheless, our preliminary evidence is new in the literature. If reproduced on larger samples, the parahippocampal deactivation that we observed in MDD females during response inhibition might either contribute to and/or result from the female-specific symptomatology (4,13,120) characterized by detrimentally high stress levels (4,13,75,132).…”
Section: Diagnosis By Sex Modulation Of Fmri Activationsmentioning
confidence: 76%
“…Some studies also reported a correlation between deficits in this area and illness severity ( 72 74 ). Therefore, the increased GM deficits in the orbitofrontal cortex observed in adult-onset MDD females may explain the higher rates of internalizing problems and rumination often observed in the female sex, which could also be explained by the presence of different illness-related genes that in turn contribute to the different symptomatology observed in males and females with MDD ( 14 , 75 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that women are more likely to experience depression during times of hormonal flux postpartum and during perimenopausal periods ( Ahokas et al, 2001 ; Parker and Brotchie, 2004 ). Circulating sex hormones and differences in inflammatory, neurotrophic, and serotonergic responses to unfavorable events between sexes have been suggested as important factors in the pathophysiology of gender-specific depression ( Bangasser and Valentino, 2014 ; Duman, 2017 ; Labonté et al, 2017 ). Therefore, a better understanding of the gender-specific pathophysiology of depression could help reveal novel and gender-specific therapeutic targets or approaches.…”
Section: Prospect Of Tcm In Depression Treatmentmentioning
confidence: 99%